2020
DOI: 10.15517/rbt.v68i2.33954
|View full text |Cite
|
Sign up to set email alerts
|

Combustibles, comportamiento del fuego y emisiones en un pastizal y una sabana artificiales en Chiapas

Abstract: Introducción: Se utilizan quemas como parte del manejo de pastos introducidos en Chiapas, lo cual puede derivar en incendios forestales. Objetivos: obtener la carga de combustibles, comportamiento del fuego, emisiones de CO2 y derivar aspectos de seguridad durante el combate de incendios en pastizales y sabanas artificiales de pasto jaragua (Hyparrhenia rufa Nees.), debido a la falta de información sobre estos temas. Métodos: Se estudiaron un pastizal y una sabana, ambos de pasto jaragua, en las comunidades Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Compared to other studies in contrasting ecosystems, flame height in the herbaceous páramo vegetation was lower, mainly due to a lower vegetation height (40 cm) and lower fuel load (22.1 t/ha). For example, Rodríguez-Trejo et al [74] reported higher flame heights in a 1 m artificial pasture in Chiapas (Mexico) with a fuel load of 6214 t/ha, and under drier climatic conditions. Anderson et al [75] also found a positive correlation between fuel load and flame height in tropical savannas, indicating that higher fuel loads produce higher flames.…”
Section: Fire Behavior and Severity During Experimental Burningmentioning
confidence: 99%
“…Compared to other studies in contrasting ecosystems, flame height in the herbaceous páramo vegetation was lower, mainly due to a lower vegetation height (40 cm) and lower fuel load (22.1 t/ha). For example, Rodríguez-Trejo et al [74] reported higher flame heights in a 1 m artificial pasture in Chiapas (Mexico) with a fuel load of 6214 t/ha, and under drier climatic conditions. Anderson et al [75] also found a positive correlation between fuel load and flame height in tropical savannas, indicating that higher fuel loads produce higher flames.…”
Section: Fire Behavior and Severity During Experimental Burningmentioning
confidence: 99%
“…La practicidad de los modelos de combustible implica estimar con cierta precisión si el fuego en un incendio forestal o quema prescrita tiene un comportamiento moderado y es factible promover su uso (Flores-Garnica 2021) en los ecosistemas forestales. Algunos estudios han evaluado el efecto de las quemas prescritas en la regeneración natural (Díaz-Hernández et al 2020), supervivencia y mortalidad de los árboles (López-Moctezuma et al 2015, Vera-Vilchis y Rodríguez-Trejo 2007) y la reducción de cargas de combustible (Rodríguez-Trejo et al 2018, Rodríguez-Trejo et al 2020, entre otros.…”
Section: Introductionunclassified
“…Globally, studies of litter production and forest fuel storage have been conducted (Scheer et al, 2011;Zhou et al, 2014). However, the dynamics of seasonal litterfall production and forest fuel storage, are not well known in the elevation gradient in regions like Chiapas, Mexico, located in causing poor decisions on forest management and conservation practices (Rodríguez et al, 2020). Ecosystem-specific studies on the seasonality of litter production and forest fuel load would help in better planning of wildfire prevention programs, ecosystem productivity, and carbon sequestration strategies.…”
Section: Introductionmentioning
confidence: 99%